End-of-life care practices of critical care nurses: A national cross-sectional survey. Issue 2 (May 2016) - Ranse, Kristen; Yates, Patsy; Coyer, Fiona
Abstract: Background: The critical care context presents important opportunities for nurses to deliver skilled, comprehensive care to patients at the end of life and their families. Limited research has identified the actual end-of-life care practices of critical care nurses. Objective: To identify the end-of-life care practices of critical care nurses. Design: A national cross-sectional online survey. Methods: The survey was distributed to members of an Australian critical care nursing association and 392 critical care nurses (response rate 25%) completed the survey. Exploratory factor analysis using principal axis factoring with oblique rotation was undertaken on survey responses to identify the domains of end-of-life care practice. Descriptive statistics were calculated for individual survey items. Results: Exploratory factor analysis identified six domains of end-of-life care practice: information sharing, environmental modification, emotional support, patient and family centred decision-making, symptom management and spiritual support. Descriptive statistics identified a high level of engagement in information sharing and environmental modification practices and less frequent engagement in items from the emotional support and symptom management practice areas. Conclusions: The findings of this study identified domains of end-of-life care practice, and critical care nurse engagement in these practices. The findings highlight future training and practice development opportunities, including the need for experiential learning targeting the emotional support practice domain. Further research is needed to enhance knowledge of symptom management practices during the provision of end-of-life care to inform and improve practice in this area.